Faktor-Faktor Yang Mempengaruhi Belanja Modal Kabupaten/Kota Di Jawa Tengah - Ilham Ahmad Maulana; Endang Masitoh; Riana R Dewi (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this research is to find out and analyze the influence of Local Revenue (PAD), General Allocation Fund (DAU), Over Time Budget Financing (SILPA) and area size on capital expenditure on district / city governments in Central Java for the period of 2016-2018.This research method is quantitative. The population of this research is 35 regencies / cities in Central Java. The sampling method used is saturated sampling so the sample in this study is all members of the population. Data analysis in this study uses multiple linear regression analysis. The results of this study indicate that the Regional Original Revenue (PAD), the Remaining Budget Financing (SILPA) and the size of the area affect the capital expenditure. While the General Allocation Fund (DAU) has no effect on capital expenditure.